2021
DOI: 10.1039/d1nr02255e
|View full text |Cite
|
Sign up to set email alerts
|

High-sorption terpyridine–graphene oxide hybrid for the efficient removal of heavy metal ions from wastewater

Abstract: Pollution of wastewater with heavy metal-ions represents one of the most severe environmental problems associated with the societal development. To overcome this issue, the design of new, highly efficient systems...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…2 The presence of different oxygenated functional groups (OFGs), such as epoxy, hydroxyl and carbonyl, 3,4 on the basal plane and the edges provides GO with a unique set of mechanical and optical properties along with a good dispersibility and colloidal stability in many solvents, particularly in water. [5][6][7] In addition, by using well-known chemistry strategies, these OFGs can serve as sites for chemical modification, endowing GO with potential applicability in chemical sensing, 8 solar cells, 9 drug delivery, 10 water desalination 11 or as an active material in energy storage systems (ESSs) 12 among others. Unfortunately, because most of the GO production methods use strong oxidants, such as potassium permanganate, GO possesses a significant number of defects in its crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…2 The presence of different oxygenated functional groups (OFGs), such as epoxy, hydroxyl and carbonyl, 3,4 on the basal plane and the edges provides GO with a unique set of mechanical and optical properties along with a good dispersibility and colloidal stability in many solvents, particularly in water. [5][6][7] In addition, by using well-known chemistry strategies, these OFGs can serve as sites for chemical modification, endowing GO with potential applicability in chemical sensing, 8 solar cells, 9 drug delivery, 10 water desalination 11 or as an active material in energy storage systems (ESSs) 12 among others. Unfortunately, because most of the GO production methods use strong oxidants, such as potassium permanganate, GO possesses a significant number of defects in its crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous systematic study on thermally reduced GO (TrGO) and CrGO, we have shown that crucial properties such as surface area, porosity, electrical and ionic conductivity, and electrochemical activity significantly affect the electrochemical performance of materials used in ESS. [ 32 ] In the present case, the electrochemical performance of rGOSH electrodes is more than twice the performance of CrGO electrodes, despite the superior electrical conductivity of the latter. While their surface area is comparable, the main differences between the two materials are the higher porosity of rGOSH, together with the nature and amount of active sites, proving that the combination of OFGs and thiol groups is an excellent solution for boosting the electrochemical performance of rGO materials for Zn 2+ ions storage.…”
Section: Resultsmentioning
confidence: 74%
“…The calculated Brunauer–Emmett–Teller (BET) surface area of rGOSH amounts to 78.96 m 2 g −1 , indicating a sixfold increase in the surface area when compared to pristine GO (12.61 m 2 g −1 ) yet being slightly smaller than CrGO (124.92 m 2 g −1 ) (Table S3, Supporting Information). [ 32 ] Interestingly, the average pore size of rGOSH amounts to 10.2 nm, thus it is nearly twice the one of GO or CrGO. Figure S10 (Supporting Information) shows the differential distribution of pore volumes versus pore sizes for rGOSH, revealing that rGOSH has a predominant mesopore distribution with sizes in the range between 10 and 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the prepared GO, GO h , and GO–Tpy, GOh–Tpy has the highest adsorption efficiency for heavy metal ions due to the synergistic effect of GO and Tpy components. The maximum adsorption capacity (q max ) of the GOh–Tpy system for Ni (II), Zn (II), and Co (II) reached 462, 421, and 336 mg g −1 at pH = 6, respectively, and showed excellent repair performance, which proved that the GOh–Tpy mixture had an ideal cycle stability, reusability, and easy separation operation [ 211 ].…”
Section: Pollutant Degradationmentioning
confidence: 99%